Assessment of the reporting of quality and outcome measures in hepatic resections: a call for 90‐day reporting in all hepatectomy series. Issue 9 (30th July 2015) - Egger, Michael E.; Ohlendorf, Joanna M.; Scoggins, Charles R.; McMasters, Kelly M.; Martin, Robert C. G.
Abstract Background The aim of this paper is to assess the current state of quality and outcomes measures being reported for hepatic resections in the recent literature. Methods Medline and PubMed databases were searched for English language articles published between 1 January 2002 and 30 April 2013. Two examiners reviewed each article and relevant citations for appropriateness of inclusion, which excluded papers of liver donor hepatic resections, repeat hepatectomies or meta‐analyses. Data were extracted and summarized by two examiners for analysis. Results Fifty‐five studies were identified with suitable reporting to assess peri‐operative mortality in hepatic resections. In only 35% (19/55) of the studies was the follow‐up time explicitly stated, and in 47% (26/55) of studies peri‐operative mortality was limited to in‐hospital or 30 days. The time period in which complications were captured was not explicitly stated in 19 out of 28 studies. The remaining studies only captured complications within 30 days of the index operation (8/28). There was a paucity of quality literature addressing truly patient‐centred outcomes. Conclusion Quality outcomes after a hepatic resection are inconsistently reported in the literature. Quality outcome studies for a hepatectomy should report mortality and morbidity at a minimum of 90 days after surgery.